Preterm Prelabor Rupture of Membranes: Outcomes with Expectant Management until 34 versus 35 Weeks - Lynch, Tara A.; Olson-Chen, Courtney; Colihan, Sarah; Meyers, Jeffrey; Holloman, Conisha; Li, Dongmei; Link, Heather; Torres, Paola; Kim, Annie; King, Devon J.; Eckman, Cari; Varlamov, Anna; Dexter, Scott; Pressman, Eva K.; Soto-Torres, Eleazar; Malshe, Amol (American Journal of Perinatology, 2019)
Objective To evaluate outcomes with expectant management of preterm prelabor rupture of membranes (PROM) until 35 weeks versus immediate delivery at ≥34 weeks.Study Design This was a multicenter retrospective cohort study of singletons with preterm PROM at >20 weeks from 2011 through 2017. Groups were defined as expectant management until 35 weeks versus immediate delivery at ≥34 weeks. Primary outcome was composite neonatal morbidity: need for respiratory support, culture positive neonatal sepsis, or antibiotic administration for >72 hours. Univariate and general estimating equation models were used with p < 0.05 considered significant.Results A total of 280 mother–infant dyads were included. There was no difference in composite neonatal outcome in pregnancies managed with expectant management compared with immediate delivery (43.4 vs. 37.5%; p = 0.32). Those with expectant management had shorter length of neonatal intensive care unit (NICU) admission but higher rates of neonatal antibiotics for > 72 hours, endometritis, and histological chorioamnionitis. There were no cases of fetal demise, neonatal death, or maternal sepsis, and only three cases of neonatal sepsis.Conclusion There is no difference in composite neonatal morbidity in pregnancies with preterm PROM managed with expectant management until 35 weeks as compared with immediate delivery at 34 weeks. Expectant management is associated with a decreased length of NICU admission but increased short-term infectious morbidity.
Keywords: expectant management; late preterm birth; preterm prelabor rupture of membranes